Screen addiction and associated factors among grade-10 school children in Nuwaragampalatha- east educational zone in Anuradhapura, Sri Lanka - Manori D. M., Shamila; Bowatta P. G., Sanjeewa; Basnayaka, Umesha Pamandi; Fernando, Janith Madushanka W.; Nishshanka, Nithum Thathsarani; Pathirana, Kasumini Sasiritha H. P.; Senarathna, Deshini Nuwanthika A. M. (International Journal Of Community Medicine And Public Health, 2024)
Background: Screen addiction has become a significant concern among school children in recent years due to the widespread use of digital devices such as smartphones, tablets, and computers. The objective was to assess the prevalence of screen addition and associated factors among grade 10 students in Nuwaragampalatha- east educational zone in Anuradhapura, Sri Lanka. Methods: A cross-sectional descriptive study was carried out among students studying in grade 10. Sample size was 318. Three schools selected randomly from Type 1AB, IC and type 2 categories and proportionate to the number of students in grade 10, sample was recruited from each school. Study instruments comprised Internet addiction test, Perceived stress scale and an interviewer administered questionnaire. Multivariate logistic regression was utilized to identify associated factors of screen addiction. Probability <0.05 was selected as the significant level. The results were expressed as odds ratios (OR) and 95% confidence intervals (CI). Results: Response rate was 100% (N=318). Mild screen addiction was reported among 29.6% (95% CI=24.6-34.9) and 20.1% (95% CI=15.9-25.0%) showed moderate level while 1.6% (95%CI=0.5-3.6) had severe addiction. Half of the students (n=155) with no screen addiction. Male sex (AOR=1.9; 95% CI=1.1-3.3; p=0.021), spending more than two hours with social media (AOR=6.1; 95% CI=3.5-13.5; p<0.001), moderate and high stress levels (AOR=3.9; 95% CI=2.3-7.0; p<0.001) and not engage in physical exercises > one hour per day (AOR=2.4; 95% CI=1.2-4.8; p=0.014) were found to be associated factors with screen addiction. Conclusions: More than half of the students had some form of screen addiction. Except sex, other associated factors are modifiable.